Physiological potential of soybean seeds produced in southern Brazil (Research, Society and Development, 2021)
Soy is the most economically important agricultural crop in the world. Achieving higher productivity has been a challenge in today's agriculture. Making the seed, surely, the most important input for agricultural development, because, as a living organism, it is depositary, directly or indirectly, of a large part of the technological advances developed by researchers over decades. Therefore, the successful implantation of a crop is in the use of seeds of high physiological quality, with a high percentage of germination and vigor. Thirty cultivars and 29 cities were used, totaling 131 samples from the three southern Brazilian states. Being evaluated the physiological quality, as well as its components, germination, accelerated aging at 41ºC for 48 hours, tetrazolium test, and mass of a thousand seeds. For the macronutrient tests, nitrogen (N), phosphorus (P), potassium (K), Calcium (Ca) and Molybdenum (Mo) were analyzed. At the end of this work, it can be concluded that the three states in the south of Brazil did not present differences regarding the physiological quality of the tested cultivars. However, the physiological potential comprises the set of skills that allows estimating the capacity of a batch of seeds to properly manifest their vital functions after sowing.